Conceptual Study on the Integration of Islamic Educational Values in Surah Al-Alaq 1-5 Through an In-Depth Learning Approach - Mujianto Mujianto; Subri Subri; Ahmad Fadholi (MISYKAT AL-ANWAR JURNAL KAJIAN ISLAM DAN MASYARAKAT, 2026)
Deep learning has become a key paradigm in twenty-first-century education because it promotes conceptual understanding, knowledge integration, and reflective thinking rather than superficial learning. However, studies linking the educational values of Q.S. Al-Alaq verses 1–5, particularly the command of iqra', with the deep learning framework remain limited. This study aims to (1) identify the educational values in Q.S. Al-Alaq verses 1–5, (2) explain deep learning from the perspective of Islamic education, and (3) formulate an integrative conceptual model. Using a qualitative conceptual design with library research, the study analyzes the Qur'an, authoritative tafsir (Ibn Kathir, Al-Azhar, and Al-Mishbah), and recent scholarly articles. Data were analyzed through documentation, reduction, categorization, and conceptual synthesis based on the Miles, Huberman, and Saldaña model, with source and theoretical triangulation ensuring credibility. The findings identify six educational values aligned with deep learning and propose a tawhid-centered pedagogical model integrating faith, knowledge, and practice through tadabbur and tafakkur.